bEcon 4 Africa: An overview of the literature on the economic assessment of GE crops in the continent, 1996-2016 - Zambrano, Patricia; Paul, Namita; Chambers, Judith A.; Falck-Zepeda, José B.; Hanson, Hillary (International Food Policy Research Institute, 2019)
The International Food Policy Research Institute (IFPRI) published the first method-focused assessment of the applied economic literature about the ex ante and ex post impacts of genetically engineered crops in developing countries in 2009. The overall findings have since been documented by other authors and have been the subject of several other studies and meta-analyses. Of the 154 papers analyzed in the cited IFPRI 2009 publications, only 25 were focused on Africa. Ten years later, this paper shows that the number of publications for Africa has nearly tripled, reaching a total of 72 publications. We gathered, classified, and reviewed all 72 Africa-focused publications. Most of the papers continue to focus on South Africa, an early adopter of the technology and, until 2007, the only African country that had commercialized GE crops. Today, even after the commercialization of insect resistant crops in Burkina Faso, Egypt, and Sudan, and the recent approval for commercialization of insect resistant cotton in Nigeria and Ethiopia, South Africa continues to be the most represented country in the literature and is the focus of 30 of the 72 publications. Nevertheless, a shift is occurring. Whereas only 4 African countries were represented in 2006, there are now 24. Additionally, the crop-focus of this literature has also expanded from mainly cotton to include a wider variety of crop/technologies, such as bacillus thuringiensis (Bt)/nutritionally enhanced banana, Bt tomato, and drought-resistant maize, among others. In addition to documenting and analyzing this Africa-focused literature, this paper documents a total of 353 performance indicators related to the actual or projected changes in yields, gross income, and input use contained in the papers focus of this review. A summary of these performance indicators has also been compiled as a searchable database available to all potential users, including practitioners, interested decision and policy makers, as well as businesses and donors not only to facilitate further research, but also as reference to advance specific GE policies, and to increase awareness related to GE technology performance.